Research of the Nature of Leadership Activities - Andrea Jankurová; Ivana Ljudvigová; Klaudia Gubová (Economics & Sociology)
Professional literature on leadership mostly states that a leader should be like (personality traits) and describes different leadership styles and types. However, very little is known about what leaders do in their everyday practice, or how they do it. Leadership should be seen more widely and should be explored along the characteristics and style of leadership and how leaders are manifested externally through their work, which means to explore the nature of leadership work. The aim of the research project was to gain more knowledge about the activities undertaken by leaders to answer a simple, but yet not too clearly answered question: „What does a leader really do?“ This finding will help reveal important activities on which best leaders focus and determine which elements are really important for leadership. The research project was managed as a combination of interviews conducted with leaders, people on senior management positions along with a questionnaire survey.